Influence of temperature and environmental conditions on aflatoxin contamination in maize collected from different regions of Pakistan during 2016–2019. (September 2020) - Asghar, Muhammad Asif; Ahmed, Aftab; Asghar, Muhammad Arif
Abstract: Aspergillus and their associated metabolites like aflatoxins (AFs) are one of the extremely significant contaminants that affect food production around the world. This species decreases yield and grains quality under suitable environmental conditions. AFs were identified in various food commodities, have been recognized as carcinogenic, mutagenic, teratogenic and immunosuppressive. From 2016 to 2019, a total of 324 samples of maize were obtained from diverse areas of Pakistan and examined for AFs level. AFs were determined using an HPLC validated method through post-column derivatization and fluorescence detection. This study also focused on the effect of climatic conditions on AF production. The total AFs (B1 +B2 +G1 +G2 ) were detected in 267 (82.4%) samples, ranged between 0.69 and 356.7 μg/kg with a mean of 15.27 ± 0.82 μg/kg. A total of 182 (56.2%) and 85 (26.2%) samples had AFs level above the maximum acceptable limit as accepted by European Union (EU) and United States of America (USA), respectively. The outcomes of the existing study indicated that the climatic situations in the examined areas had a great impact on AFs contamination. Significant differences were found between AFs contamination levels in the samples collected in different months ( p < 0.05 ). The most contaminated samples were identified in July, August and September as the climatic conditions favored the AF production. These outcomes suggested that the food commodities must be regularly examined in order to prevent the health of human and animal from the hazardous effects produced by AFs contamination. Graphical abstract: Image 1 Highlights: Assessed of AFs in maize with respect to climatic conditions during 2015–2018. Total AFs (B1 +B2 +G1 +G2 ) was detected in 82.4% samples out of 324 tested samples. The contamination range of AFs was 0.69–356.7 μg/kg with an average of 15.27 μg/kg. 56% and 26% samples exceeded the maximum limit set by the EU and USA, respectively. The AFs levels were also compared with the national and international community.